A Rapid Extraction Method for mammalian cell cultures, suitable for quantitative immunoblotting analysis of proteins, including phosphorylated GCN2 and eIF2α - Silva, Richard C. (MethodsX, 2017)
Many studies require the detection and relative quantitation of proteins from cell culture samples using immunoblotting. Limiting factors are the cost of protease inhibitors, the time required to break cells and generate samples, as well as the high risk of protein loss during cell breakage procedures. In addition, a common problem is the viscosity of lysed samples due to the released genomic DNA. As a consequence, the DNA needs to be broken down prior to denaturing polyacrylamide protein gel electrophoresis (SDS-PAGE), e.g. by passing the sample through a syringe gauge needle, sonication, or DNase treatment. In a quest to find a more cost-effective, fast, and yet robust procedure, we found that cell lysis, protein denaturation, and DNA fragmentation can be done in only two steps: harvesting followed by a simple non-laborious 2nd step. Similarly to many pre-existing cell breakage procedures, in our Rapid Protein Extraction (RPE) method, proteins liberated from cells are immediately exposed to a denaturing environment. However, advantages of our method are: • No breaking buffer is needed, instead proteins are liberated directly into the denaturing protein loading buffer used for SDS-PAGE. Consequently, our RPE method does not require any expensive inhibitors. • The RPE method does not involve post-lysis centrifugation steps; instead all cell material is dissolved during the 2nd step, the mixing-heat-treatment step which is new to this method. This prevents potential protein loss that may occur during centrifugation. In addition, this 2nd step simultaneously shears the genomic DNA, making an additional step for DNA fragmentation unnecessary. • The generated samples are suitable for high-quality quantitative immunoblotting. With our RPE method we successfully quantified the phosphorylated forms of protein kinase GCN2 and its substrate eIF2α. In fact, the western signals were stronger and with less background, as compared to samples generated with a pre-existing method.